Epilogue: Joseph Lichtenberg: A Vision of a Sense of Power in the Relationship Between Patient and Analyst. - Gray, Arthur A. (Psychoanalytic Inquiry)
The article in Psychoanalytic Inquiry discusses the concept of a personal sense of power in the relationship between patient and analyst, as envisioned by Joseph Lichtenberg. The monograph explores how this sense of power influences one's sense of self, agency, affect, intentions, and goals. Through collaborative efforts with colleagues like Mady Chalk, Elizabeth Carr, Frank Lachmann, and Jim Fosshage, the article delves into how understanding and restoring a loss of power can transform the psychoanalytic encounter and illuminate the human condition. Arthur A. Gray, Ph.D., CGP, serves as the issue editor and contributes to the discussion on diversity, power, and affective engagement in psychoanalysis.